THE ANALYSIS OF ACTORS IN THE MAKING OF THE BUDGET REVENUE OF REGIONAL COST - Saad, Muhammad (Journal of Humanity, 2015)
This article is the result of research on the analysis of the policy making of the budget revenues and shopping area of Makassar city fiscal year 2009. One part of this research use approach to the actors and the relationships between actors in policy making. Within the framework of the system of policy making of Budget income and Expenditure area (Budgets) Makassar city, this research is the description of the analysis of the local government and actors Peopleâs Representative Council District Makassar city as policy makers in making Grant Makassar city